Suplementação proteico : energética para ovinos alimentados com forragem tropical de baixa qualidade - Jesus, Josiani Marques de (2018)
The objective of this study was to evaluate the effects of supplying different levels of protein energy supplementation (PE) for sheep fed with low nutritional quality forage. Five noncastrated sheep, with a mean body weight of 55kg, were distributed in a Latin square design (5x5), fed with Marandu grass with supplementation of 100, 200, 300 and 400g/animal/day of PE, in addition to a control treatment with mineral supplement (MM) supplied ad libitum. PE supplements increased (P<0,05) the dry matter (DM) intake, however, the forage intake was maintained (P>0,05). There was a linear increase (P<0,05) in the organic matter (OM), crude protein (CP), digestible organic matter (DOM) and PB:DOM ratio in kg / day. Regarding the intake in g / kg of body weight, there was a linear increase (P<0,05) in the DM intake, with no influence on forage dry matter (FDM) intake and NDF (P>0,05). The digestibility of DM, OM and DOM increased linearly according to supplementation (P<0,05), however the digestibility of NDF and CP did not change (P>0,05). Ingested, fecal, absorbed and retained nitrogen increased linearly according to PE supplementation (P<0,05), however, urinary nitrogen did not change (P>0,05). According to higher PE supply, there was a reduction in forage intake time (P<0,05) with a consequent increase in the time of supplement intake. The rumination time in relation to DM intake (min/kg DM) was reduced (P<0,05) according to the use of PE. The supplementation of PE in forage of low nutritional quality provides an increase in DM intake, being attributed to the higher level of PE in the diet, providing improvement in the digestibility and balance of nitrogen compounds for sheep in tropical conditions.